Religious dualism in South Africa: consequences of inadequate mission theology of the spirit world - Froise, Harald (University of the Free State, 2005)
This thesis has been written to address the reality that we tend to arrive at philosophical positions based on our worldview which is largely affected by our culture and background. This is so ingrained into our system that it is difficult for us to break away from that position. In a Christian context, this affects the way we interpret scripture, and it is only when we step back and objectively examine carefully what we believe against what is written in scripture that we begin to question how accurately our worldview reflects biblical teaching. This tendency to base our beliefs on our culture has enormous significance when we come to export our faith to other cultures. The thesis examines the beliefs of people in an animistic society, and attempts to differentiate between what is purely cultural and what is religious. It takes note of the fact that heavy emphasis is being placed on respecting the existing cultures in societies in which the Christian faith is being propagated. But in so doing there is a blurring of what is cultural and what is religious, so that demands are made to add Christianity to an existing religion rather than to switch from serving foreign gods to worshipping the one true God. The thesis also examines western evangelical Christianity which has been strongly influenced by enlightenment thinking, so that the supernatural events of the New Testament have given way to scientifically explained alternatives. It notes that much of the Christian faith that has been taken to pe ople of different cultures has carried the baggage of that western culture. This has had serious deficiencies when dealing with societies that have been steeped in animism, which the thesis contends is nothing more than demonic influences. The brand of Christianity that has been brought has been inadequate to deal with these phenomena. The result of this is that people have not been liberated from the influences of their animistic past. It is postulated that the Christianity of the Bible does indeed deal w ith issues of animism, and that to a significant degree. It was faced in New Testament times and powerfully dealt with by the Christian’s authority over the demonic forces. It further holds that this New Testament ministry is still valid for today, and tha t the results of missionary activity could have been very different if this biblical theology had been understood and practised. Instead, the failure to equip emerging churches with the ability to deal with these forces, has led them to attempt to deal wit h them in their own way. The only way they knew was to continue the practice of appeasing the spirits. This is why there is such a strong appeal to include appeasement of the spirits, referred to as ‘ancestors,’ in the enculturated Christianity of the emerging churches. This has contributed to religious dualism in South Africa, since a demonstration that the Christian faith is powerful enough to deal with the demonic forces would have obviated the need to find solutions elsewhere. It is also noted that where it has been possible to break out of the limitations of western enlightenment theology, evangelism has been more effective.

Hierdie proefskrif is geskryf om aan te dui dat die filosofiese standpunte wat ons inneem bepaal word deur ons kultuur en agtergrond. Dit is só deel van ons dat dit baie moeilik is om daarvan ontslae te raak. In ’n Christelike omgewing beVnvloed dit die wyse waarop ons die Bybel interpreteer en slegs wanneer ons volledig objektief waarneem wat ons in die lig van die Bybel glo, kan bepaal word of ons wêreldbeskouing die Bybel getrou navolg. Die begronding van geloofsoortuigings in die heersende kultuur het veral groot betekenis wanneer ons ons geloof aan ander kulture oordra. Die proefskrif ondersoek die geloofsoortuigings van animistiese gemeenskappe en poog om te onderskei tussen wat werklik slegs kultuur is en wat werklik godsdiens is. Daardie kulture waaronder die Christelike geloof verkondig word moet gerespekteer word. Daar moet egter gewaak word teen die vermenging van kulturele sake en religieuse sake. Soms word die eis gestel om die Christelike Evangelie bloot aan te heg by bepaalde godsdienste sonder ’n totale oorgawe aan die aanbidding van die ware God in die plek van vreemde gode. Die proefskrif ondersoek ook Westerse Evangeliese Christendom wat sterk beVnvloed is deur die Verligting met die gevolg dat die bonatuurlike elemente van die Nuwe Testament vervang word met wetenskaplike verklarings. Daar is vasgestel dat die Westerse kultuur op verskeie ander kulture oorgedra is met die verkondiging van die Evangelie. Daar bestaan dus besliste tekortkominge in die hantering van die animistiese kulture wat volgens die oortuiging van dié geskrif demonies van aard is. Die gevolg is dat verskeie mense nie van die invloed van hulle demoniese agtergrond verlos word nie. Die standpunt wat hier ingeneem word is dat die Bybel animisme wel op ’n deurslaggewende wyse hanteer. In die Nuwe-Testamentiese tye het die saak ook voorgekom en is dit hanteer deur die Christen se oorwinning daaroor. Hierdie Nuwe-Testamentiese hantering van die saak is steeds geldig en die sending kon heel anders verloop het indien dit deurgaans erken is. Inteendeel, opkomende kerke is nie bemagtig om wel dié magte te hanteer nie en dit het daartoe gelei dat hulle op hulle eie wyse daarmee gehandel het. Die enigste wyse wat aan hulle bekend was om die geestesmagte te hanteer, was om die geeste te probeer kalmeer. Daarom is daar steeds in die opkomende kerke die oortuiging dat die geeste - die voorouers – bloot kalmeer moet word. Dit het gelei tot religieuse dualisme in Suid -Afrika aangesien ’n duidelike demonstrasie van die oorwinning van die Christelike evangelie oor die geestelike magte ontbreek het en hulp dus elders gesoek is. Waar die beperking van die Westerse Verligtingsdenke oorkom is, was evangelisasie ook baie meer effektief.
Thesis (Ph.D. (Missiology))--University of the Free State, 2005
Keywords: Christianity and other religions -- South Africa; Religions -- Methodology; Animism; Deliverence; Ancestors; Syncretism; Worldviews; Enlightenment; Evangelism; Biblical theory; Culture; Spirit world; Authority; Demons